A multi-omics approach to unravel the interaction between heat and drought stress in the Arabidopsis thaliana holobiont - Biancamaria Senizza; Fabrizio Araniti; Simon Lewin; Sonja Wende; Steffen Kolb; Steffen Kolb; Luigi Lucini (Frontiers in Plant Science)
The impact of combined heat and drought stress was investigated in Arabidopsis thaliana and compared to individual stresses to reveal additive effects and interactions. A combination of plant metabolomics and root and rhizosphere bacterial metabarcoding were used to unravel effects at the plant holobiont level. Hierarchical cluster analysis of metabolomics signatures pointed out two main clusters, one including heat and combined heat and drought, and the second cluster that included the control and drought treatments. Overall, phenylpropanoids and nitrogen-containing compounds, hormones and amino acids showed the highest discriminant potential. A decrease in alpha-diversity of Bacteria was observed upon stress, with stress-dependent differences in bacterial microbiota composition. The shift in beta-diversity highlighted the pivotal enrichment of Proteobacteria, including Rhizobiales, Enterobacteriales and Azospirillales. The results corroborate the concept of stress interaction, where the combined heat and drought stress is not the mere combination of the single stresses. Intriguingly, multi-omics interpretations evidenced a good correlation between root metabolomics and root bacterial microbiota, indicating an orchestrated modulation of the whole holobiont.